Renal function during sevoflurane or total intravenous propofol anaesthesia: a single-centre parallel randomised controlled study. (May 2022) - Franzén, Stephanie; Semenas, Egidijus; Taavo, Micael; Mårtensson, Johan; Larsson, Anders; Frithiof, Robert
Abstract: Background: The choice of anaesthetic may influence regulation of renal perfusion and function. We investigated renal function in patients anaesthetised with propofol or sevoflurane before surgery and postoperatively. Methods: Patients with ASA physical status 1–2 planned for spinal surgery were randomised to propofol or sevoflurane anaesthesia. Blood and urine were collected before anaesthesia, during anaesthesia (before surgery), during postoperative care, and the day after surgery. Results: Twenty-seven patients completed the study protocol (average age, 51 yr; average BMI, 28 kg m −2 ) and 11 were women. Urine output and sodium excretion were lower during sevoflurane anaesthesia ( n =14) than during propofol anaesthesia ( n =13) (0.3 vs 1.1 ml kg −1 h −1 [ P =0.01] and 2.6 vs 6.0 mmol h −1 [ P =0.04], respectively). Urinary potassium excretion was lower during anaesthesia than after, without intergroup difference (2.3 vs 5.7 mmol h −1, P <0.001). Sevoflurane anaesthesia increased plasma renin compared with baseline (138 vs 23 mIU L −1, P <0.001) and propofol anaesthesia (138 vs 27 mIU L −1, P =0.008). Plasma arginine–vasopressin did not change significantly during anaesthesia, but was elevated postoperatively compared with baseline irrespective of anaesthetic (21 vs 12 ng L −1, P =0.02). Sevoflurane caused higher postoperative plasma creatinine than propofol (83 vs 66 mmol L −1, P =0.01). Kidney injury molecule-1 and neutrophil gelatinase-associated lipocalin did not change significantly in either group. Conclusions: Sevoflurane anaesthesia reduced urine output and sodium excretion and increased plasma renin compared with propofol anaesthesia. The impact of this on acute kidney injury and fluid resuscitation during surgery warrants further investigation. Clinical trial registration: EudraCT: 2017-001646-10; Clinicaltrials.gov: NCT0333680.